PENERAPAN METODE DEMONSTRASI PADA PELAJARAN SHALAT KELAS IV MADRASAH IBTIDAIYAH MUHAMMADIYAH SUKAJATI HAURGEULIS - Elvin Nur Kharisma; Abdur Rahim (Bajang Institute, 2022)
This study discusses the application of the demonstration method in class IV prayer lessons at Madrasah Ibtidaiyah Muhammadiyah Sukajati Haurgeulis. Demonstration is a very effective method, because it helps students to find answers on their own based on the correct facts or data. The demonstration method is a method of presenting lessons by demonstrating and showing students about a process, a certain object situation, either actual or just an imitation. This study aims to determine how to apply the demonstration method to prayer lessons and to find out the supporting and inhibiting factors in prayer lessons using the demonstration method in class IV Madrasah Ibtidaiyah Muhammadiyah Sukajati Haurgeulis. The subjects of this research are all fourth grade students of Madrasah Ibtidaiyah Muhammadiyah Sukajati Haurgeulis, and the object of this research is 30 students. This research is a qualitative descriptive research by taking location in Sukajati Village, District, Haurgeulis, Indramayu. Data collection techniques using observation, interviews, and documentation. Data analysis in this research is the exploration stage, entering the field, determining focus, selection, and compenential analysis. Checking the validity of the data using triangulation. The results showed that the application of the demonstration method in class IV prayer lessons at Madrasah Ibtidaiyah Muhammadiyah Sukajati Haurgeulis, namely with students accepting the movements taught by the teacher so that the situation in the class was no longer as messy as usual, the application of the demonstration method also made it easier for students to understand and accept the prayer movements that were carried out. exemplified by the teacher. Factors supporting the demonstration method in prayer lessons are adequate facilities for practicing demonstrations, such as prayer rooms and prayer equipment. Behind the supporting factors there are inhibiting factors, namely the less time and the different backgrounds of students.